Morphological and DNA sequence analysis of the Cytochrome oxidase (cox1) of a new record of Acropora in Lian, Batangas and Bolinao, Pangasinan - Luzon, Katrina S. (Animo Repository, 2004)
Colonies of Acropora, first spotted at Talim Bay, Lian, Batangas, is suspected to be a new record for the Philippines. Conventional taxonomic identification of the coral reveals that it may be Acropara abrotanoides or Acropora robusta. The probability of these suggested species was confirmed through DNA sequencing. The mitochondrial control region cytochrome oxidase 1 (cruel) is known to be a very conserved gene region. Amplified sequences of cox1 were analyzed and revealed a 98% to100% likelihood of being Acropora tenuis, a species that is very morphologically dis